Comparative evaluation of national intellectual capital measurement models - Aleknavičiūtė, Rasa; Mačerinskienė, Irena (Business: Theory and Practice, 2015)
National intellectual capital is regarded as an important factor of a country’s ability to perform high value added functions including the ability to create innovations. Measuring national intellectual capital is still a complicated task. In this article national intellectual capital concept and measurement models are analysed in order to show how national intellectual capital could be measured. The findings show that there are several weaknesses of measurement models validity. Those weaknesses in more recent measurement models are minimized by introducing advanced national intellectual capital structural models and more complex value approximation methods. Analysis of selected national intellectual capital measurement models has shown that there are not many similar indicators used (from 21% to 60% of matching indicators), though results obtained by using these evaluation models have high significant correlation.